Non-aqueous electrolyte and lithium ion secondary battery
Patent Information
- Application Number
- CN202611467436.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
过高的VC添加量,会显著增大电池界面阻抗,降低电池低温放电性能与倍率输出能力
本申请的非水电解液,硫氰酸盐包含硫氰酸根阴离子,硫氰酸根阴离子中的S原子和N原子对锂离子具有较高的配位亲和性,可有效调控电解液中锂离子的溶剂化鞘层结构,降低溶剂分子在锂离子第一溶剂化壳层中的占比,促使硫氰酸根及电解液本征锂盐阴离子共同参与锂离子溶剂化配位,提高二者在锂离子溶剂化鞘层中的配位占比,生成更多接触离子对与离子聚集体,显著提高电解液本征锂盐阴离子在负极界面处的还原反应参与程度。在负极表面,其还原产物可使SEI膜无机组分富集LiF、Li2S、Li3N等难溶锂盐,各类多相无机晶体相互嵌合形成大量晶界通道,可为锂离子提供高速传输路径,大幅降低锂离子跨膜迁移阻力。但是,硫氰酸盐自身还原成膜能力较弱,单独使用时无法形成完整稳定的SEI膜,且所形成的SEI膜缺少柔韧有机相作为应力缓冲层,在电池充放电过程中易受应力作用发生脆性破裂。而碳酸亚乙烯酯作为经典成膜添加剂,具有较高的还原电位,可在负极表面优先还原分解形成有机聚合物组分,构筑有机聚合物外层。但是,单独使用碳酸亚乙烯酯作为成膜剂时存在内层无机组分单一、有机外层高温稳定性差的固有缺陷。两者联用时,硫氰酸盐调控的溶剂化结构改变了负极界面的反应路径与前驱体分布,为VC的还原分解提供了有利的界面环境,从而使碳酸亚乙烯酯的还原聚合更加均匀有序,同时碳酸亚乙烯酯形成的有机骨架为硫氰酸盐还原生成的无机组分提供了附着与分散的载体,避免了无机组分的团聚与脱落。且当硫氰酸盐的含量低于0.01%时,其对溶剂化结构的调控作用不明显,无法有效改善SEI膜的无机组分构成;当硫氰酸盐类化合物的含量高于1.5%时,过量的硫氰酸根阴离子在负极表面发生副反应,反而劣化电池性能。而当碳酸亚乙烯酯的含量低于0.1%时,无法形成完整的SEI膜;当碳酸亚乙烯酯的含量高于4.0%时,会导致SEI膜过厚,显著增加电池的界面阻抗。二者在合适的含量范围内协同形成薄而致密、兼具高无机组分占比与良好柔韧性的复合SEI膜。该复合SEI膜相比于单纯添加VC生成的SEI膜,无机层更致密、非均相性更高、锂离子传输速度更快,在高温长循环和高温存储过程中不易破损重组,从而减少活性锂的损耗和电解液的副反应消耗,显著提升电池的高温循环容量保持率、降低循环过程中的阻抗增长率,并提高高温存储容量保持率和容量恢复率。这种微观层面的相互促进使得复合SEI膜的综合性能远超单一添加剂成膜,实现了1+1>2的技术效果。
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to non-aqueous electrolytes and their lithium-ion secondary batteries. Background Technology
[0002] Lithium-ion batteries, with their high energy density, excellent rate performance, and environmentally friendly properties, have become core components in new energy vehicles, large-scale electrochemical energy storage, and other fields. With the rapid expansion of the electric commercial vehicle, grid-side, and user-side energy storage markets, cycle life, as a core indicator determining the battery's total lifespan cost and operational reliability, has become a key area for breakthroughs in electrolyte technology upgrades.
[0003] Electrolyte is the key medium for transporting lithium ions in lithium-ion batteries, and its interfacial compatibility with the positive and negative electrodes directly determines the battery's internal resistance, cycle life, and safety performance. Introducing functional electrolyte additives to construct a homogeneous and structurally stable solid electrolyte interphase (SEI) film in situ on the electrode surface is the most economical and efficient technical path to improve interfacial stability and enhance battery cycle performance. Among numerous film-forming additives, vinylene carbonate (VC) is currently the most widely used commercially available negative electrode film-forming additive: it has a high reduction potential (approximately 1.0-1.2V vs. Li). + Li can preferentially undergo reduction and decomposition on the negative electrode surface, participating in the formation of a dense SEI film, while also inhibiting the dissolution of transition metals, which can improve the cycle retention capability of the battery to a certain extent.
[0004] However, in existing lithium-ion battery systems, especially lithium iron phosphate (LFP) power and energy storage systems, the conventional addition amount of vinylene carbonate (VC) in the electrolyte is typically 2wt%-4wt%. Excessive VC addition significantly increases the battery's interfacial impedance, reducing its low-temperature discharge performance and rate capability. Simultaneously, the SEI film formed by VC exhibits poor high-temperature thermal stability. Under long-cycle and high-temperature storage conditions, the SEI film is prone to damage and continuous regeneration. This process repeatedly consumes electrolyte and negative electrode active lithium, and the continuous thickening of the SEI film further leads to increased battery impedance and capacity decay, severely restricting battery performance improvement. Therefore, how to construct a high-quality composite SEI film with both low interfacial impedance and excellent thermal stability has become a key technical problem that urgently needs to be solved to improve the initial impedance, high-temperature cycle stability, and high-temperature storage performance of lithium-ion batteries. Summary of the Invention
[0005] The technical problem to be solved by this application is to provide a non-aqueous electrolyte and a lithium-ion secondary battery thereof. This application can improve the high-temperature cycle performance and high-temperature storage performance of lithium-ion batteries and reduce the impedance growth rate during the cycle process.
[0006] To address the aforementioned technical problems, according to one aspect of this application, a non-aqueous electrolyte is provided, comprising: an organic solvent; a lithium salt; a thiocyanate; and vinylene carbonate; wherein the thiocyanate has the structure shown in Formula I.
[0007] Formula I In Equation I, M + The electrolyte contains at least one of the following: alkali metal ions, ammonium cations, quaternary phosphorus cations, imidazolium cations, pyridinium cations, pyrrolidineium cations, and piperidinium cations, wherein the mass fraction of thiocyanate is 0.01%-1.5% and the mass fraction of vinylene carbonate is 0.1%-4.0% based on the total mass of the non-aqueous electrolyte.
[0008] According to the embodiments of this application, the mass fraction of thiocyanate is 0.1%-1.0%.
[0009] According to the embodiments of this application, the mass fraction of vinylene carbonate is 0.5%-2.5%.
[0010] According to an embodiment of this application, the mass ratio of thiocyanate to the vinylene carbonate is (0.01-10):1.
[0011] According to an embodiment of this application, the mass ratio of thiocyanate to the vinylene carbonate is (0.04-2):1.
[0012] According to embodiments of this application, the thiocyanate is selected from lithium thiocyanate, sodium thiocyanate, potassium thiocyanate, rubidium thiocyanate, cesium thiocyanate, ammonium thiocyanate, methylammonium thiocyanate, ethylammonium thiocyanate, n-butylammonium thiocyanate, dimethylammonium thiocyanate, triethylamine thiocyanate, tetramethylammonium thiocyanate, tetraethylammonium thiocyanate, tetrabutylammonium thiocyanate, tetrabutylphosphine thiocyanate, 1-ethyl-3-methylimidazolium thiocyanate, 1-propyl-3-methylimidazolium thiocyanate, and 1-butyl-3-methylimidazolium thiocyanate. At least one of the following: 1-pentyl-3-methylimidazolium thiocyanate, 1-hexyl-3-methylimidazolium thiocyanate, 1-octyl-3-methylimidazolium thiocyanate, 1-decyl-3-methylimidazolium thiocyanate, 1-butyl-2,3-dimethylimidazolium thiocyanate, 1-vinyl-3-methylimidazolium thiocyanate, pyridinium thiocyanate, 1-methylpyridinium thiocyanate, 1-ethylpyridinium thiocyanate, 1-butylpyridinium thiocyanate, pyrrolidine thiocyanate, and piperidine thiocyanate.
[0013] According to embodiments of this application, the non-aqueous electrolyte further includes auxiliary additives. The mass fraction of the auxiliary additives is 0.1%-5.0% based on the total mass of the non-aqueous electrolyte. The auxiliary additives are selected from at least one of fluoroethylene carbonate, ethylene sulfate, and 1,3-propane sulpholactone.
[0014] According to embodiments of this application, the mass fraction of lithium salt is 6%-20% based on the total mass of the non-aqueous electrolyte, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide.
[0015] According to the embodiments of this application, the organic solvent has a mass fraction of 70%-90% based on the total mass of the non-aqueous electrolyte, and the organic solvent is selected from at least two of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate, propyl formate, ethyl formate, methyl formate, ethyl acetate, methyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, propyl butyrate, and ethyl butyrate.
[0016] According to another aspect of this application, a lithium-ion secondary battery is provided, comprising: a positive electrode and a negative electrode capable of storing and releasing lithium ions, a separator, and the aforementioned non-aqueous electrolyte.
[0017] Compared with the prior art, the beneficial effects of this application are as follows: The non-aqueous electrolyte of this application contains thiocyanate anions. The S and N atoms in the thiocyanate anions have a high coordination affinity for lithium ions, which can effectively regulate the solvation sheath structure of lithium ions in the electrolyte, reduce the proportion of solvent molecules in the first solvation shell of lithium ions, and promote the joint participation of thiocyanate and intrinsic lithium salt anions in lithium ion solvation coordination. This increases their coordination ratio in the lithium ion solvation sheath, generating more contact ion pairs and ion aggregates, and significantly improving the participation of intrinsic lithium salt anions in the reduction reaction at the negative electrode interface. On the negative electrode surface, the reduction products can enrich the inorganic components of the SEI film with sparingly soluble lithium salts such as LiF, Li2S, and Li3N. Various multiphase inorganic crystals interlock to form numerous grain boundary channels, providing a high-speed transport path for lithium ions and significantly reducing the resistance to lithium ion migration across the membrane. However, thiocyanate itself has weak reductive film-forming ability and cannot form a complete and stable SEI film when used alone. Furthermore, the resulting SEI film lacks a flexible organic phase as a stress buffer layer, making it susceptible to brittle fracture under stress during battery charging and discharging. Vinylene carbonate, as a classic film-forming additive, has a high reduction potential and can preferentially reduce and decompose on the negative electrode surface to form organic polymer components, constructing an organic polymer outer layer. However, using vinylene carbonate alone as a film-forming agent has inherent drawbacks, such as a single inorganic component in the inner layer and poor high-temperature stability of the organic outer layer. When used in combination, the solvation structure regulated by thiocyanate alters the reaction pathway and precursor distribution at the negative electrode interface, providing a favorable interfacial environment for the reductive decomposition of VC. This results in a more uniform and orderly reductive polymerization of vinylene carbonate. Simultaneously, the organic framework formed by vinylene carbonate provides a carrier for the adhesion and dispersion of the inorganic components generated by thiocyanate reduction, preventing the aggregation and detachment of inorganic components. Furthermore, when the thiocyanate content is below 0.01%, its regulatory effect on the solvation structure is not significant, and it cannot effectively improve the inorganic component composition of the SEI film. When the content of thiocyanate compounds is above 1.5%, excessive thiocyanate anions undergo side reactions on the negative electrode surface, which degrades battery performance. When the content of vinylene carbonate is below 0.1%, a complete SEI film cannot be formed; when the content of vinylene carbonate is above 4.0%, it leads to an excessively thick SEI film, significantly increasing the interfacial impedance of the battery. The two components, within a suitable content range, synergistically form a thin and dense composite SEI film with both a high proportion of inorganic components and good flexibility. Compared to SEI films generated by simply adding VC, this composite SEI film has a denser inorganic layer, higher heterogeneity, and faster lithium-ion transport speed. It is less prone to breakage and recombination during high-temperature long-cycle and high-temperature storage, thereby reducing the loss of active lithium and the consumption of electrolyte by side reactions. It significantly improves the high-temperature cycle capacity retention rate of the battery, reduces the impedance growth rate during cycling, and improves the high-temperature storage capacity retention rate and capacity recovery rate.This mutual promotion at the microscopic level makes the overall performance of the composite SEI film far exceed that of the film formed by a single additive, achieving a technical effect of 1+1>2. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this application pertains. The terms "comprising" and similar expressions used herein mean that the element or object preceding the word covers the element or object listed following the word and its equivalents, but does not exclude other elements or objects.
[0019] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0020] According to one embodiment of the present application, the non-aqueous electrolyte includes: an organic solvent; a lithium salt; thiocyanate; and vinylene carbonate; wherein, based on the total mass of the non-aqueous electrolyte, the mass fraction of thiocyanate is 0.01%-1.5%, and the mass fraction of vinylene carbonate is 0.1%-4.0%.
[0021] Specifically, the structural formula of thiocyanate is shown below.
[0022]
[0023] Among them, M+ M is a monovalent cation. + It is selected from at least one of alkali metal ions, ammonium cations, quaternary phosphonium cations, imidazolium cations, pyridinium cations, pyrrolidineium cations, and piperidinium cations.
[0024] As an example, based on the total mass of the non-aqueous electrolyte, the mass fraction of thiocyanate can be 0.01%, 0.1%, 0.6%, 0.9%, 1.2%, or 1.5%, preferably 0.1%-1.0%; the mass fraction of vinylene carbonate can be 0.1%, 0.5%, 1%, 2%, 3%, or 4.0%, preferably 0.5%-2.5%.
[0025] This application does not specify the source of thiocyanate; it may be prepared using commercially available products well known to those skilled in the art or by conventional preparation methods in the art.
[0026] The non-aqueous electrolyte of this application contains thiocyanate anions. The S and N atoms in the thiocyanate anions have a high coordination affinity for lithium ions, which can effectively regulate the solvation sheath structure of lithium ions in the electrolyte, reduce the proportion of solvent molecules in the first solvation shell of lithium ions, and promote the joint participation of thiocyanate and intrinsic lithium salt anions in lithium ion solvation coordination. This increases their coordination ratio in the lithium ion solvation sheath, generating more contact ion pairs and ion aggregates, and significantly improving the participation of intrinsic lithium salt anions in the reduction reaction at the negative electrode interface. On the negative electrode surface, the reduction products can enrich the inorganic components of the SEI film with sparingly soluble lithium salts such as LiF, Li2S, and Li3N. Various multiphase inorganic crystals interlock to form numerous grain boundary channels, providing a high-speed transport path for lithium ions and significantly reducing the resistance to lithium ion migration across the membrane. However, thiocyanate itself has weak reductive film-forming ability and cannot form a complete and stable SEI film when used alone. Furthermore, the resulting SEI film lacks a flexible organic phase as a stress buffer layer, making it susceptible to brittle fracture under stress during battery charging and discharging. Vinylene carbonate, as a classic film-forming additive, has a high reduction potential and can preferentially reduce and decompose on the negative electrode surface to form organic polymer components, constructing an organic polymer outer layer. However, using vinylene carbonate alone as a film-forming agent has inherent drawbacks, such as a single inorganic component in the inner layer and poor high-temperature stability of the organic outer layer. When used in combination, the solvation structure regulated by thiocyanate alters the reaction pathway and precursor distribution at the negative electrode interface, providing a favorable interfacial environment for the reductive decomposition of VC. This results in a more uniform and orderly reductive polymerization of vinylene carbonate. Simultaneously, the organic framework formed by vinylene carbonate provides a carrier for the adhesion and dispersion of the inorganic components generated by thiocyanate reduction, preventing the aggregation and detachment of inorganic components. Furthermore, when the thiocyanate content is below 0.01%, its regulatory effect on the solvation structure is not significant, and it cannot effectively improve the inorganic component composition of the SEI film. When the content of thiocyanate compounds is above 1.5%, excessive thiocyanate anions may cause side reactions on the negative electrode surface, thus degrading battery performance. When the content of vinylene carbonate is below 0.1%, a complete SEI film cannot be formed; when the content of vinylene carbonate is above 4.0%, it leads to an excessively thick SEI film, significantly increasing the interfacial impedance of the battery. The two components, within a suitable content range, synergistically form a thin and dense composite SEI film with both a high proportion of inorganic components and good flexibility. Compared to SEI films generated by simply adding VC, this composite SEI film has a denser inorganic layer, higher heterogeneity, and faster lithium-ion transport speed. It is less prone to breakage and recombination during high-temperature long-cycle and high-temperature storage, thereby reducing the loss of active lithium and the consumption of electrolyte by side reactions. It significantly improves the high-temperature cycle capacity retention rate of the battery, reduces the impedance growth rate during cycling, and improves the high-temperature storage capacity retention rate and capacity recovery rate.This mutual promotion at the microscopic level makes the overall performance of the composite SEI film far exceed that of the film formed by a single additive, achieving a technical effect of 1+1>2.
[0027] In some embodiments, the mass ratio of thiocyanate to vinylene carbonate is (0.01-10):1. Within this range, the mass ratio is more conducive to the formation of an organic synergy between thiocyanate and vinylene carbonate on the electrode surface, constructing a composite SEI film with suitable thickness, density, flexibility, and high ionic conductivity. This further reduces the initial impedance of the lithium-ion battery and improves high-temperature cycling and storage performance. If the thiocyanate content is too low and the vinylene carbonate content is too high, the regulatory effect of thiocyanate on the solvation structure is insufficient to improve the defects in VC film formation; conversely, if the thiocyanate content is too high and the vinylene carbonate content is too low, a complete organic polymer framework cannot be formed, and the desired synergistic effect is also difficult to obtain.
[0028] As an example, the mass ratio of thiocyanate to vinylene carbonate can be 0.01, 0.05, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. Preferably, the mass ratio of thiocyanate to vinylene carbonate is (0.04-2):1.
[0029] In some embodiments, the thiocyanate is selected from lithium thiocyanate (CAS No.: 123333-85-7), sodium thiocyanate (CAS No.: 540-72-7), potassium thiocyanate (CAS No.: 333-20-0), rubidium thiocyanate (CAS No.: 3879-02-5), cesium thiocyanate (CAS No.: 3879-01-4), ammonium thiocyanate (CAS No.: 1762-95-4), methylammonium thiocyanate (CAS No.: 61540-63-4), ethylammonium thiocyanate (CAS No.: 25153-19-9), and n-butylammonium thiocyanate (CAS No.: 25162-84-9). Dimethylammonium thiocyanate (CAS No.: 117943-34-7), Triethylamine thiocyanate (CAS No.: 32061-78-2), Tetramethylammonium thiocyanate (CAS No.: 15597-46-3), Tetraethylammonium thiocyanate (CAS No.: 4587-19-3), Tetrabutylammonium thiocyanate (CAS No.: 3674-54-2), Tetrabutylphosphine thiocyanate (CAS No.: 32609-24-8), 1-Ethyl-3-methylimidazolium thiocyanate (CAS No.: 331717-63-6), 1-Propyl-3-methylimidazolium thiocyanate (CAS No.: 847499) -73-4), 1-Butyl-3-methylimidazolium thiocyanate (CAS No.: 344790-87-0), 1-pentyl-3-methylimidazolium thiocyanate (e.g., supplier: Jinjinle (Hunan) Chemical Co., Ltd.), 1-hexyl-3-methylimidazolium thiocyanate (CAS No.: 847499-74-5), 1-octyl-3-methylimidazolium thiocyanate (CAS No.: 847499-72-3), 1-decyl-3-methylimidazolium thiocyanate (CAS No.: 847499-75-6), 1-butyl-2,3-dimethylimidazolium thiocyanate (CAS No.: 67385) At least one of the following: 5-36-2), 1-vinyl-3-methylimidazolium thiocyanate (CAS No.: 2770474-00-3), pyridinium thiocyanate (CAS No.: 30248-54-5), 1-methylpyridinium thiocyanate (CAS No.: 23812-12-6), 1-ethylpyridinium thiocyanate (CAS No.: 51249-28-6), 1-butylpyridinium thiocyanate (CAS No.: 359399-64-7), pyrrolidine thiocyanate (CAS No.: 217309-80-3), and piperidine thiocyanate (CAS No.: 22205-64-7). Thiocyanate can be a single substance, for example, sodium thiocyanate. Thiocyanate can also be a mixture of multiple substances, for example, a mixture of lithium thiocyanate and sodium thiocyanate.
[0030] In some embodiments, the non-aqueous electrolyte auxiliary additive, based on the total mass of the non-aqueous electrolyte, has a mass fraction of 0.1%-5.0%. For example, the mass fraction of the auxiliary additive can be 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, or 5.0%. The auxiliary additive is selected from at least one of fluoroethylene carbonate, ethylene sulfate, and 1,3-propane sulcolone. The auxiliary additive helps improve the stability of the SEI film on the negative electrode surface and the CEI film on the positive electrode, thereby further improving the initial impedance, high-temperature cycle performance, and high-temperature storage performance of the lithium-ion battery.
[0031] In some embodiments, the mass fraction of lithium salt, based on the total mass of the non-aqueous electrolyte, is 6%-20%. For example, the mass fraction of lithium salt can be 6%, 8%, 10%, 12%, 14%, 16%, 18%, or 20%. Specifically, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide. By controlling the type and content of the electrolyte salt within the above range, the non-aqueous electrolyte can have a suitable ionic conductivity, meeting the lithium-ion transport requirements of the lithium-ion battery during charging and discharging, thereby improving the initial impedance, high-temperature cycle performance, and high-temperature storage performance of the lithium-ion battery.
[0032] In some embodiments, the mass fraction of the organic solvent, based on the total mass of the non-aqueous electrolyte, is 70%-90%. For example, the mass fraction of the organic solvent can be 70%, 75%, 80%, 85%, or 90%. The organic solvent is selected from at least two of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate, propyl formate, ethyl formate, methyl formate, ethyl acetate, methyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, propyl butyrate, and ethyl butyrate. By controlling the type and content of the solvent within the above range, the non-aqueous electrolyte can possess suitable viscosity, high ionic conductivity, and good chemical stability, thereby improving the initial impedance, high-temperature cycle performance, and high-temperature storage performance of lithium-ion batteries.
[0033] A lithium-ion secondary battery according to another embodiment of this application includes a positive electrode and a negative electrode capable of storing and releasing lithium ions, a separator, and the aforementioned non-aqueous electrolyte.
[0034] Specifically, the positive electrode (positive electrode sheet) includes: a positive current collector and a positive electrode coating disposed on at least one surface of the positive current collector. The positive electrode coating includes: a positive electrode active material, a conductive agent, and a binder.
[0035] Specifically, this application does not impose any particular restrictions on the thickness of the positive electrode coating and the positive electrode current collector, as long as the purpose of this application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 30 μm to 200 μm, and the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm.
[0036] Specifically, the positive electrode active material is selected from at least one of lithium iron phosphate, ternary materials (NCM, NCA), lithium manganese oxide, and lithium cobalt oxide. These positive electrode active materials can be used alone, or two or more can be combined in any combination and proportion.
[0037] There are no particular limitations on the conductive agent, and conductive agents commonly used by those skilled in the art can be used. As an example, the conductive agent may be at least one selected from conductive carbon black, graphene, acetylene black, Ketjen black, conductive carbon fiber, carbon dots, and carbon nanotubes. These conductive agents can be used alone or in any combination and proportion. Preferably, the conductive agent is a mixture of conductive carbon black and carbon nanotubes.
[0038] There are no particular limitations on the adhesive, and adhesives commonly used by those skilled in the art can be used. As examples, the adhesive may be at least one of polyvinyl chloride, polyacrylamide, polyvinylidene fluoride, polytetrafluoroethylene, a copolymer of tetrafluoroethylene and hexafluoropropylene, a terpolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a terpolymer of vinylidene fluoride-tetrafluoroethylene-propylene, styrene-butadiene rubber, polyimide, polypropylene resin, carboxymethyl cellulose, and fluorinated acrylate resin. These adhesives may be used alone or in combination of two or more in any proportion. Preferably, polyvinylidene fluoride is used as the adhesive.
[0039] There are no particular limitations on the positive electrode current collector, and current collectors commonly used by those skilled in the art can be used. As an example, the positive electrode current collector can be a metal foil such as aluminum foil, nickel foil, tin foil, or a composite current collector. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate layer. Specifically, the composite current collector can be formed by depositing a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) onto a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). Preferably, aluminum foil is used as the positive electrode current collector.
[0040] The positive electrode sheet can be prepared according to methods commonly used in the art. For example, the positive electrode sheet can be formed by uniformly dispersing the positive electrode active material, conductive agent, and binder in a solvent (e.g., N-methylpyrrolidone (NMP)) at a predetermined mass ratio to obtain a positive electrode slurry; coating the positive electrode slurry onto a positive electrode current collector, drying it, and then rolling and cutting it to obtain the positive electrode sheet.
[0041] Specifically, the negative electrode (negative electrode sheet) includes: a negative electrode current collector and a negative electrode coating disposed on at least one surface of the negative electrode current collector. The negative electrode coating includes: a negative electrode active material, a conductive agent, and a binder.
[0042] Specifically, this application does not impose any particular restrictions on the thickness of the negative electrode material layer and the negative electrode current collector, as long as the purpose of this application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 150 μm, and the thickness of the negative electrode current collector is 4 μm to 16 μm.
[0043] Specifically, the negative electrode active material is selected from at least one of natural graphite, artificial graphite, mesophase micro carbon spheres, hard carbon, soft carbon, silicon-based materials, tin-based materials, or lithium titanate. Among them, the silicon-based material is selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys; the tin-based material is selected from at least one of elemental tin, tin oxide compounds, or tin alloys.
[0044] There are no particular limitations on the conductive agent, and conductive agents commonly used by those skilled in the art can be used. As an example, the conductive agent may be at least one selected from conductive carbon black, graphene, acetylene black, Ketjen black, carbon fiber, carbon dots, and carbon nanotubes. The carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The carbon fiber is selected from vapor-grown carbon fiber (VGCF) and / or carbon nanofibers. These conductive agents can be used alone or in any combination and proportion.
[0045] There are no particular limitations on the adhesive, and any adhesive commonly used by those skilled in the art can be used. As an example, the adhesive may be at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), or carboxymethyl chitosan (CMCS). These adhesives may be used alone or in combination or proportion of two or more. Preferably, the adhesive is a mixture of carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber.
[0046] Specifically, the negative electrode coating also includes a thickener selected from sodium carboxymethyl cellulose (CMC-Na).
[0047] There are no particular limitations on the negative electrode current collector, and any negative electrode current collector commonly used by those skilled in the art can be used. As an example, the negative electrode current collector can be a metal foil (e.g., copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam) or a composite current collector. Composite current collectors typically employ a "sandwich" structure, using an insulating polymer film (such as PET, PP, PBT) as the intermediate substrate, and depositing a certain thickness of copper layer on both its upper and lower surfaces using a combination of magnetron sputtering and electroplating. Preferably, the negative electrode current collector is copper foil.
[0048] The negative electrode sheet can be prepared according to methods commonly used in the art. For example, the negative electrode sheet can be formed by uniformly dispersing the negative electrode active material, conductive agent, and binder in a solvent (e.g., water) at a predetermined mass ratio to obtain a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, drying it, and then rolling and cutting it to obtain the negative electrode sheet.
[0049] Specifically, there are no particular limitations on the membrane, and commonly used porous membranes with electrochemical and chemical stability can be used, such as polymer membranes, ceramic membranes, non-woven fabrics, inorganic-organic composite membranes, etc. Preferably, the membrane is selected from polymer membranes. There are no particular limitations on the thickness of the membrane, as long as it achieves the purpose of this application; for example, the thickness of the membrane can be from 10 μm to 12 μm.
[0050] Specifically, the lithium-ion secondary battery also includes a casing for housing the positive electrode, separator, negative electrode, non-aqueous electrolyte, and other components known in the field of lithium-ion secondary batteries. This application does not limit the scope of these other components. This application does not impose any particular limitation on the casing; it can be a casing known in the art, as long as it achieves the purpose of this application. For example, the casing can be a rigid casing or a flexible casing. The material of the rigid casing can be metal; this application does not limit the type of metal and can use known metal rigid casings, as long as they achieve the purpose of this application. The flexible casing can be a metal plastic film, such as aluminum-plastic film, steel-plastic film, etc.
[0051] Specifically, the physical structure of the lithium-ion secondary battery described in this application can be presented in different levels, such as a battery cell, a battery module composed of at least one cell, or a battery pack composed of at least one module, depending on the application requirements. The specific number of cells in each level can be selected by those skilled in the art according to capacity requirements.
[0052] At the electrochemical system level, battery cells in any of the above physical levels can be of the types such as lithium metal secondary batteries and lithium-ion secondary batteries (including liquid lithium-ion batteries, lithium polymer batteries, and lithium-ion polymer batteries).
[0053] The present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Where no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in the art or in accordance with the product instructions shall apply. Instruments used without a specified manufacturer are conventional products that can be obtained commercially. Reagents used without a specified manufacturer are all conventional products that can be obtained commercially or products that can be synthesized according to conventional preparation methods.
[0054] Example 1 Preparation of non-aqueous electrolyte In an inert atmosphere filled with argon (water content <10 ppm, oxygen content <10 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed evenly in a mass ratio of 3:4:3 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) at a mass of 12.5 wt% of the total mass of the non-aqueous electrolyte was added to the organic solvent and completely dissolved. Then, lithium thiocyanate at a mass of 0.01 wt% and vinylene carbonate (VC) at a mass of 1.0 wt% of the total mass of the non-aqueous electrolyte were added and stirred evenly to obtain the non-aqueous electrolyte.
[0055] Preparation of positive electrode sheet Lithium iron phosphate, carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and then added to N-methyl-2-pyrrolidone (NMP) solvent for high-speed shear dispersion to obtain a homogenized positive electrode slurry. The positive electrode slurry was uniformly coated onto both sides of an aluminum foil current collector using an automatic coating machine. The slurry was then sequentially dried, cold-pressed, edge-trimmed, cut into sheets, slit, and vacuum-dried before being welded with tabs to obtain the positive electrode sheet.
[0056] Preparation of negative electrode sheet Graphite, carbon black, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 95:1.5:1.5:2, and then added to a solvent of water and stirred until homogeneous to obtain a negative electrode slurry. The negative electrode slurry was coated on both sides of a copper foil current collector, and after drying, cold pressing, edge trimming, cutting, slitting, vacuum drying, and welding of tabs, a negative electrode sheet was obtained.
[0057] Battery assembly A 13μm thick Al2O3 ceramic / PE base film / Al2O3 ceramic three-layer polymer separator was selected as the battery separator, wherein the PE base film is 9μm thick and the two Al2O3 ceramic layers are both 2μm thick. In a dry environment with dew point controlled below -50℃, the positive electrode, separator, and negative electrode were stacked and aligned in the order of positive electrode / separator / negative electrode / separator / positive electrode (ensuring a separator between the positive and negative electrodes) to form a bare cell. The bare cell was then placed in an aluminum-plastic film casing, vacuum baked, and injected with the prepared non-aqueous electrolyte. After vacuum sealing, settling, formation, aging, and capacity testing, a lithium-ion secondary battery with a nominal capacity of 2.1Ah was obtained.
[0058] Example 2 The same descriptions as in Example 1 are omitted in Example 2. The difference between Example 2 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.1 wt%, and the amount of vinylene carbonate added is adjusted to 1.5 wt%.
[0059] Example 3 The same descriptions as in Example 1 are omitted in Example 3. The difference between Example 3 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.1 wt%, and the amount of vinylene carbonate added is adjusted to 2.5 wt%.
[0060] Example 4 The same descriptions as in Example 1 are omitted in Example 4. The difference between Example 4 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.1 wt%, and the amount of vinylene carbonate added is adjusted to 3.5 wt%.
[0061] Example 5 The same descriptions as in Example 1 are omitted in Example 5. The difference between Example 5 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt%, and the amount of vinylene carbonate added is adjusted to 1.5 wt%.
[0062] Example 6 The same descriptions as in Example 1 are omitted in Example 6. The difference between Example 6 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 1.0 wt%, and the amount of vinylene carbonate added is adjusted to 1.5 wt%.
[0063] Example 7 The same descriptions as in Example 1 are omitted in Example 7. The difference between Example 7 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 1.5 wt%, and the amount of vinylene carbonate added is adjusted to 4.0 wt%.
[0064] Example 8 The same descriptions as in Example 1 are omitted in Example 8. The difference between Example 8 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt%, and the amount of vinylene carbonate added is adjusted to 0.5 wt%.
[0065] Example 9 The same descriptions as in Example 1 are omitted in Example 9. The difference between Example 9 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt%, and the amount of vinylene carbonate added is adjusted to 0.25 wt%.
[0066] Example 10 The same descriptions as in Example 1 are omitted in Example 10. The difference between Example 1 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt%, and the amount of vinylene carbonate added is adjusted to 0.17 wt%.
[0067] Example 11 The same descriptions as in Example 11 are omitted. The difference between Example 11 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt%, and the amount of vinylene carbonate added is adjusted to 2.5 wt%.
[0068] Example Twelve The same descriptions as in Example 1 are omitted in Example 12. The difference between Example 12 and Example 1 is that in the preparation of the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.5 wt% and the amount of vinylene carbonate added is adjusted to 3.5 wt%.
[0069] Example Thirteen The same descriptions as in Example 1 are omitted in Example 13. The difference between Example 13 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 1.0 wt%, and the amount of vinylene carbonate added is adjusted to 0.1 wt%.
[0070] Example Fourteen The same descriptions as in Example 14 are omitted. The difference between Example 14 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 1.2 wt%, and the amount of vinylene carbonate added is adjusted to 1.5 wt%.
[0071] Example 15 The same descriptions as in Example 1 are omitted in Example 15. The difference between Example 15 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 0.01 wt%, and the amount of vinylene carbonate added is adjusted to 1.5 wt%.
[0072] Example Sixteen The same descriptions as in Example 1 are omitted in Example 16. The difference between Example 16 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of lithium thiocyanate added is adjusted to 1.5 wt%, and the amount of vinylene carbonate added is adjusted to 0.1 wt%.
[0073] Example 17 The same descriptions as in Example 5 are omitted in Example 17. The difference between Example 17 and Example 5 is that lithium thiocyanate is replaced with sodium thiocyanate when preparing the non-aqueous electrolyte.
[0074] Example 18 The same descriptions as in Example 18 and Example 5 are omitted. The difference between Example 18 and Example 5 is that in the preparation of the non-aqueous electrolyte, lithium thiocyanate is replaced with ammonium thiocyanate.
[0075] Example 19 The same descriptions as in Example 19 and Example 5 are omitted. The difference between Example 19 and Example 5 is that lithium thiocyanate is replaced with tetrabutylammonium thiocyanate when preparing the non-aqueous electrolyte.
[0076] Example 20 The same descriptions as in Example 5 are omitted in Example 20. The difference between Example 20 and Example 5 is that lithium thiocyanate is replaced with tetrabutylphosphine thiocyanate when preparing the non-aqueous electrolyte.
[0077] Example 21 The same descriptions as in Example 5 are omitted in Example 21. The difference between Example 21 and Example 5 is that lithium thiocyanate is replaced with 1-ethyl-3-methylimidazolium thiocyanate when preparing the non-aqueous electrolyte.
[0078] Example 22 The same descriptions as in Example 5 are omitted in Example 22. The difference between Example 22 and Example 5 is that lithium thiocyanate is replaced with 1-butyl-2,3-dimethylimidazolium thiocyanate when preparing the non-aqueous electrolyte.
[0079] Example 23 The same descriptions as in Example 5 are omitted in Example 23. The difference between Example 23 and Example 5 is that lithium thiocyanate is replaced with 1-vinyl-3-methylimidazolium thiocyanate when preparing the non-aqueous electrolyte.
[0080] Example 24 The same descriptions as in Example 5 are omitted in Example 24. The difference between Example 24 and Example 5 is that lithium thiocyanate is replaced with 1-methylpyridinium thiocyanate when preparing the non-aqueous electrolyte.
[0081] Example 25 The same descriptions as in Example 5 are omitted in Example 25. The difference between Example 25 and Example 5 is that lithium thiocyanate is replaced with pyrrolidine thiocyanate when preparing the non-aqueous electrolyte.
[0082] Example 26 The same descriptions as in Example 5 are omitted in Example 26. The difference between Example 26 and Example 5 is that lithium thiocyanate is replaced with piperidine thiocyanate when preparing the non-aqueous electrolyte.
[0083] Example 27 The same descriptions as in Example 5 are omitted in Example 27. The difference between Example 27 and Example 5 is that when preparing the non-aqueous electrolyte, 1.0 wt% of fluoroethylene carbonate (FEC) is added.
[0084] Comparative Example 1 The same descriptions as those in Comparative Example 1 are omitted. The difference between Comparative Example 1 and Example 1 is that lithium thiocyanate and vinylene carbonate are not added when preparing the non-aqueous electrolyte.
[0085] Comparative Example 2 The same descriptions as in Comparative Example 1 are omitted in Comparative Example 2. The difference between Comparative Example 2 and Example 1 is that the amount of lithium thiocyanate added is adjusted to 0.5 wt% when preparing the non-aqueous electrolyte, and vinylene carbonate is not added.
[0086] Comparative Example 3 The same descriptions as those in Comparative Example 3 and Example 1 are omitted. The difference between Comparative Example 3 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of vinylene carbonate added is adjusted to 1.5 wt%, and lithium thiocyanate is not added.
[0087] Comparative Example 4 The parts of Comparative Example 4 that are the same as those in Example 1 are omitted. The differences between Comparative Example 4 and Example 1 are: When preparing the non-aqueous electrolyte, the amount of vinylene carbonate added was adjusted to 1.5 wt%, and the amount of lithium thiocyanate added was adjusted to 2.0 wt%.
[0088] Comparative Example 5 The same descriptions as those in Comparative Example 5 and Example 1 are omitted. The difference between Comparative Example 5 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of vinylene carbonate added is adjusted to 5.0 wt%, and the amount of lithium thiocyanate added is adjusted to 0.5 wt%.
[0089] Comparative Example 6 The same descriptions as those in Comparative Example 6 and Example 1 are omitted. The difference between Comparative Example 6 and Example 1 is that when preparing the non-aqueous electrolyte, the amount of vinylene carbonate added is adjusted to 1.5 wt%, and the amount of lithium thiocyanate added is adjusted to 0.005 wt%.
[0090] The amounts of vinylene carbonate, thiocyanate, and auxiliary additives added in Examples 1 to 27 and Comparative Examples 1 to 6 are shown in Table 1.
[0091] Table 1.
[0092] Electrochemical performance testing The electrochemical performance of the lithium-ion batteries prepared in Examples 1 to 27 and Comparative Examples 1 to 6 was tested.
[0093] 1. Initial DCR Test In a constant temperature chamber at 25°C, the lithium-ion batteries prepared in Examples 1 to 27 and Comparative Examples 1 to 6 were charged at a constant current of 0.33C to the upper limit voltage and then charged at a constant voltage to the cutoff current of 0.05C. The lithium-ion batteries were then discharged at 0.5C for 1 hour, left to stand for 1 hour, and then discharged at a constant current of 2C for 10 seconds. The DC internal resistance (DCR) of the lithium-ion battery at 50% SOC was calculated, which is the initial DC internal resistance DCR0.
[0094] 2. 60℃ Cyclic Performance Test In a constant-temperature chamber at 60°C, the lithium-ion batteries prepared in Examples 1 to 27 and Comparative Examples 1 to 6 were charged at a constant current rate of 1C to the upper limit voltage, then charged at a constant voltage rate to the cutoff current of 0.05C, and then discharged at a constant current rate of 1C to the lower limit voltage. This charge-discharge cycle was repeated for 400 cycles. After the cycle, the batteries were recapacitated at 25°C, and the DC internal resistance DCR1 at 50% SOC was tested. The capacity retention rate and DCR growth rate after 400 cycles at 60°C were calculated.
[0095] Capacity retention rate after 400 cycles at 60℃ = discharge capacity of the 400th cycle / discharge capacity of the 1st cycle × 100%.
[0096] DCR growth rate = (DCR1 - DCR0) / DCR0 × 100% 3. Storage performance test at 60℃ The lithium-ion batteries prepared in Examples 1 to 27 and Comparative Examples 1 to 6 were all charged at a constant current of 0.33C to the upper limit voltage, then charged at a constant voltage to the cutoff current of 0.05C, and then stored in a 60°C constant temperature chamber for 60 days. The capacity retention rate and capacity recovery rate were tested every 7 days. The capacity retention rate and capacity recovery rate of the lithium-ion batteries after 60 days of storage were calculated.
[0097] Capacity retention rate = (First discharge capacity after storage / Discharge capacity before storage) × 100% Capacity recovery rate = Discharge capacity after one complete charge and discharge cycle after storage / Discharge capacity before storage × 100%.
[0098] The electrochemical test data of the lithium-ion batteries in Examples 1 to 27 and Comparative Examples 1 to 6 are shown in Table 2.
[0099] Table 2.
[0100] The test results in Table 2 show that: (1) Comparative Example 1 is a blank basic electrolyte without any functional additives. The capacity retention rate after 400 cycles at 60℃ is only 13.48%, the DCR growth rate is as high as 126.24%, and the high temperature storage performance is also the worst.
[0101] (2) Comparative Example 2 only added 0.5% lithium thiocyanate (thiocyanate), without adding VC. Due to the poor film-forming performance of thiocyanate when used alone, it cannot form a complete and stable SEI film. Although its initial DCR is low (41.2mΩ), the capacity retention rate after 400 cycles at 60℃ is only 54.16%, the DCR growth rate is 98.39%, and the high-temperature storage capacity retention rate is only 72.48%, indicating that the performance improvement is still not ideal. This comparative example demonstrates that although thiocyanate compounds can improve battery performance to some extent when used alone, the lack of an organic film-forming framework prevents the construction of a stable and complete SEI film, resulting in unsatisfactory improvements in high-temperature cycling and high-temperature storage performance.
[0102] (3) Comparative Example 3 only added 1.5% VC, without adding thiocyanate. The high-temperature stability of the film formed by VC alone was insufficient. The capacity retention rate was 68.21% after 400 cycles at 60°C, the DCR growth rate was 80.15%, and the high-temperature storage capacity retention rate was 75.46%. This comparative example proves that although vinylene carbonate can form an organic polymer SEI film when used alone, the performance is not ideal because the inorganic component is singular and the high-temperature stability of the organic outer layer is insufficient. During long-term high-temperature cycling, the SEI film is easily damaged and reassembled.
[0103] (4) Example 5: The addition of 0.5% lithium thiocyanate and 1.5% VC, i.e., the synergistic use of thiocyanate and vinylene carbonate, resulted in a capacity retention rate of 78.71% after 400 cycles at 60°C, which was 24.55 percentage points and 10.50 percentage points higher than Comparative Example 2 (pure A) and Comparative Example 3 (pure VC), respectively. The DCR growth rate was only 63.45%, which was 34.94 percentage points and 16.70 percentage points lower than Comparative Example 2 and Comparative Example 3, respectively. The high-temperature storage capacity retention rate reached 80.96%, which was 8.48 percentage points and 5.50 percentage points higher than Comparative Example 2 and Comparative Example 3, respectively. It is worth noting that if the capacity retention rate is estimated by simply linearly superimposing the effects of the two additives used alone, it would only reach about 61.2% (a weighted sum of 54.16% and 68.21%), while the actual combined use reached 78.71%, which significantly exceeded the expectation of simple superposition. The DCR growth rate was also much lower than the weighted average of the two additives used alone. Example 5 shows significantly better performance than the simple superposition of Comparative Examples 2 and 3, fully demonstrating an unexpected synergistic effect between thiocyanate and vinylene carbonate. The combined use of the two results in performance far exceeding that of using them alone, which is the core of this invention.
[0104] (5) Examples 1-16 investigated the effects of different addition amounts and mass ratios of thiocyanate and VC. The results showed that when the thiocyanate content was 0.01%–1.5%, the VC content was 0.1%–4.0%, and the mass ratio of the two was in the range of (0.01–10):1, good high-temperature cycling and high-temperature storage performance could be obtained. The capacity retention rate after 400 cycles at 60℃ was above 71%, and the DCR growth rate was below 76%. Among them, the performance was better when the thiocyanate content was 0.1%–1.0%, the VC content was 0.5%–2.5%, and the mass ratio was (0.04–2):1. Example 5 (thiocyanate = 0.5%, VC = 1.5%, thiocyanate / VC = 0.33) had the best overall performance. Although Examples 15 and 16 meet the content range of claim 1, the thiocyanate / VC mass ratios are 0.0067 and 15, respectively, which exceed the range of (0.01 to 10):1 defined in claim 4. The capacity retention rates decrease to 71.81% and 69.51%, respectively, while the DCR growth rates increase to 74.65% and 77.35%, respectively. This demonstrates that controlling the mass ratio of the two within a reasonable range is crucial for achieving synergistic effects.
[0105] (6) Examples 17–26 investigated the effects of different cation types on thiocyanates. The results showed that Na… + NH4 +When thiocyanates containing various cations such as quaternary ammonium cations, quaternary phosphorus cations, imidazolium cations, pyridinium cations, pyrrolidineium cations, and piperidinium cations are used in combination with VC, similar synergistic effects can be achieved. The capacity retention rate after 400 cycles at 60°C is above 76%, and the DCR growth rate is below 67%, demonstrating that the various thiocyanate compounds covered by claim 1 can exert a synergistic effect when used in combination with vinylene carbonate, indicating that the technical solution of this invention has broad applicability. Furthermore, Example 27, based on Example 5, further adds 1.0% FEC as an auxiliary additive. After 400 cycles at 60°C, the capacity retention rate reaches 80.25%, the DCR growth rate decreases to 60.15%, the high-temperature storage capacity retention rate reaches 82.35%, and the capacity recovery rate reaches 85.45%, demonstrating that the auxiliary additive FEC can further improve the high-temperature cycling and high-temperature storage performance of the battery.
[0106] (7) Comparative Examples 4-6 investigated the effects of technical solutions exceeding the scope of this invention. In Comparative Example 4, the thiocyanate (lithium thiocyanate) content was 2.0%, exceeding 1.5%. Although it was still used in conjunction with 1.5% VC, the excess thiocyanate anions caused side reactions on the negative electrode surface. The capacity retention rate after 400 cycles at 60°C was only 70.11%, and the DCR growth rate was as high as 77.65%, significantly worse than Example 5 (78.71%, 63.45%). In Comparative Example 5, the VC content was 5.0%, exceeding 4.0%. When used in conjunction with 0.5% lithium thiocyanate, the excess VC led to an excessively thick SEI film. The initial DCR was as high as 46.7 mΩ, the capacity retention rate after 400 cycles at 60°C was only 66.51%, and the DCR growth rate was as high as 90.05%. The high-temperature storage performance also decreased significantly. In Comparative Example 6, the thiocyanate content was only 0.005%, and the mass ratio to VC was 0.0033, lower than 0.01. The regulatory effect of thiocyanate on the solvation structure was weak, and the synergistic effect was difficult to demonstrate. The capacity retention rate after 400 cycles at 60°C was only 69.81%, close to that of Comparative Example 3 (pure VC, 68.21%). Comparative Examples 4-6 demonstrate from the opposite perspective that only by controlling the content and mass ratio of thiocyanate and vinylene carbonate within the range defined in the claims of this invention can the synergistic effect of the two be fully utilized, resulting in excellent high-temperature cycling and high-temperature storage performance.
[0107] The above description is merely a specific implementation of the embodiments of this application, but the protection scope of the embodiments of this application is not limited thereto. Any changes or substitutions within the technical scope disclosed in the embodiments of this application should be covered within the protection scope of the embodiments of this application. Therefore, the protection scope of the embodiments of this application should be determined by the protection scope of the appended claims.
Claims
1. A non-aqueous electrolyte, characterized in that, include: Organic solvents; Lithium salts; Thiocyanate and vinylene carbonate, wherein the thiocyanate has the structure shown in Formula I; Formula I In Equation I, M + It is selected from at least one of alkali metal ions, ammonium cations, quaternary phosphonium cations, imidazolium cations, pyridinium cations, pyrrolidineium cations, and piperidinium cations. Wherein, based on the total mass of the non-aqueous electrolyte, the mass fraction of the thiocyanate is 0.01%-1.5%, and the mass fraction of the vinylene carbonate is 0.1%-4.0%.
2. The non-aqueous electrolyte according to claim 1, characterized in that, The mass fraction of the thiocyanate is 0.1%-1.0%.
3. The non-aqueous electrolyte according to claim 1, characterized in that, The mass fraction of the vinylene carbonate is 0.5%-2.5%.
4. The non-aqueous electrolyte according to claim 1, characterized in that, The mass ratio of the thiocyanate to the vinylene carbonate is (0.01-10):
1.
5. The non-aqueous electrolyte according to claim 4, characterized in that, The mass ratio of the thiocyanate to the vinylene carbonate is (0.04-2):
1.
6. The non-aqueous electrolyte according to claim 1, characterized in that, The thiocyanate is selected from lithium thiocyanate, sodium thiocyanate, potassium thiocyanate, rubidium thiocyanate, cesium thiocyanate, ammonium thiocyanate, methylammonium thiocyanate, ethylammonium thiocyanate, n-butylammonium thiocyanate, dimethylammonium thiocyanate, triethylamine thiocyanate, tetramethylammonium thiocyanate, tetraethylammonium thiocyanate, tetrabutylammonium thiocyanate, tetrabutylphosphine thiocyanate, 1-ethyl-3-methylimidazolium thiocyanate, 1-propyl-3-methylimidazolium thiocyanate, 1-butyl-3-methylimidazolium thiocyanate, and 1-pentyl... At least one of the following: 3-methylimidazolium thiocyanate, 1-hexyl-3-methylimidazolium thiocyanate, 1-octyl-3-methylimidazolium thiocyanate, 1-decyl-3-methylimidazolium thiocyanate, 1-butyl-2,3-dimethylimidazolium thiocyanate, 1-vinyl-3-methylimidazolium thiocyanate, pyridinium thiocyanate, 1-methylpyridinium thiocyanate, 1-ethylpyridinium thiocyanate, 1-butylpyridinium thiocyanate, pyrrolidine thiocyanate, and piperidine thiocyanate.
7. The non-aqueous electrolyte according to claim 1, characterized in that, It also includes auxiliary additives, and the mass fraction of the auxiliary additives is 0.1%-5.0% based on the total mass of the non-aqueous electrolyte. The auxiliary additives are selected from at least one of fluoroethylene carbonate, ethylene sulfate, and 1,3-propane sulpholactone.
8. The non-aqueous electrolyte according to claim 1, characterized in that, The lithium salt has a mass fraction of 6%-20% based on the total mass of the non-aqueous electrolyte, and the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide.
9. The non-aqueous electrolyte according to claim 1, characterized in that, Based on the total mass of the non-aqueous electrolyte, the organic solvent has a mass fraction of 70%-90%, and the organic solvent is selected from at least two of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, fluoroethylene carbonate, propyl formate, ethyl formate, methyl formate, ethyl acetate, methyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, propyl butyrate, and ethyl butyrate.
10. A lithium-ion secondary battery, characterized in that, include: Positive and negative electrodes, a separator, and a non-aqueous electrolyte according to any one of claims 1-9, capable of storing and releasing lithium ions.
